The Preventive Effect of Oxytocin to Cisplatin-Induced Neurotoxicity: An Experimental Rat Model. (22nd January 2015) - Akman, Tulay; Akman, Levent; Erbas, Oytun; Terek, Mustafa Cosan; Taskiran, Dilek; Ozsaran, Aydin
Abstract : Peripheral neurotoxicity is a frequent dose-limiting side effect of the chemotherapeutic agent cisplatin. This study was conducted to investigate the preventive effect of oxytocin (OT) on cisplatin-induced neurotoxicity in rats. Forty-four adult female rats were included in the study. Thirty-six rats were administered intraperitoneally (i.p.) single dose cisplatin 10 mg/kg and divided in to 3 groups. The first group (n = 12 ) received saline i.p., whereas the second group (n = 12 ) and the third group (n = 12 ) were injected with 80  µ g/kg and 160  µ g/kg OT, respectively, for 10 days. The remaining 8 rats served as the control group. Electromyography (EMG) studies were recorded and blood samples were collected for the measurement of plasma lipid peroxidation (malondialdehyde; MDA), tumor necrosis factor (TNF)- α, and glutathione (GSH) levels. EMG findings revealed that compound muscle action potential amplitude was significantly decreased and distal latency was prolonged in the nontreated cisplatin-injected rats compared with the control group (P < 0.005 ). Also, nontreated cisplatin-injected rats showed significantly higher TNF- α and MDA levels and lower GSH level than control group. The administration of OT significantly ameliorated the EMG alterations, suppressed oxidative stress and inflammatory parameters, and increased antioxidative capacity. We suggest that oxytocin may have beneficial effects against cisplatin-induced neurotoxicity.